Graphene-Supported Ultrafine Metal Nanoparticles Encapsulated by Mesoporous Silica: Robust Catalysts for Oxidation and Reduction Reactions - Shang, Lu; Bian, Tong; Zhang, Baihui; Zhang, Donghui; Wu, Li-Zhu; Tung, Chen-Ho; Yin, Yadong; Zhang, Tierui (Angewandte Chemie International Edition, 2014)
Graphene nanosheet‐supported ultrafine metal nanoparticles encapsulated by thin mesoporous SiO2 layers were prepared and used as robust catalysts with high catalytic activity and excellent high‐temperature stability. The catalysts can be recycled and reused in many gas‐ and solution‐phase reactions, and their high catalytic activity can be fully recovered by high‐temperature regeneration, should they be deactivated by feedstock poisoning. In addition to the large surface area provided by the graphene support, the enhanced catalytic performance is also attributed to the mesoporous SiO2 layers, which not only stabilize the ultrafine metal nanoparticles, but also prevent the aggregation of the graphene nanosheets. The synthetic strategy can be extended to other metals, such as Pd and Ru, for preparing robust catalysts for various reactions. Layer cake: The synthesis of graphene‐nanosheet‐supported ultrafine metal nanoparticles encapsulated by thin mesoporous silica layers is reported. The resulting class of robust catalysts was shown to possess high activity, good stability under high temperature conditions, and excellent recyclability and reusability in both gas‐ and solution‐phase reactions.